Is it the end of enterprise resource planning? evidence from Indonesia state-owned enterprises (SOEs) - Istianingsih Sastrodiharjo; Uswatun Khasanah (Cogent Business & Management, 2023)
AbstractImplementing an enterprise resource planning (ERP) system is crucial if a company wants to compete globally and keep up with technological advances. This study examines the effect of information sharing and competent personnel on ERP. This study takes a quantitative approach using a questionnaire tested with covariance-based structural equation modelling. The sample includes 338 respondents from several Indonesian state-owned enterprises. The results show that information sharing positively affects the success of ERP system implementation. Next, competent personnel also positively affect the success of ERP implementation. Overall, this research is helpful for firms who want to implement an ERP system to manage information and personal arrangements accordingly so that the system can run as expected.